Evaluation of Tear Production as Measured by Schirmer Test I in Dogs after Acepromazine and Acepromazine–Methadone Premedication - Claudia Giannetto (MDPI AG, 2021)
The purpose of the current study was to investigate the effects of two commonly used sedation protocols in dogs, acepromazine (ACP) and acepromazine–methadone (ACP–MET) combination, on tear production measured by the Schirmer Tear Test (STT) 1. We hypothesized that both sedation protocols cause a reduction in canine tear production for a variable time. Fifteen client-owned dogs were recruited for the study. Each dog was subjected to sedation twice, 2–3 weeks apart, and they were randomly allocated to one of two groups receiving ACP (0.015 mg kg−1) or ACP–MET (0.010 mg kg−1 and 0.2 mg kg−1) intramuscularly. In both eyes, tear production was measured 15 min before sedation (T0) and 20 min (T20 m), 40 min (T40 m), 1 h (T1), 2 h (T2), 4 h (T4) and 8 h (T8), after drug administration. Two-way repeated measures ANOVA, followed by the Bonferroni post hoc test (p < 0.05), showed a significant effect of time (p < 0.0001) and treatment (p < 0.0001). A significant decrease in tear production at T20 m, T40 m, T1 and T2 compared to T0 was observed in the ACP experimental protocol, while in the ACP + MET protocol, this reduction persisted until T8. Comparing the two experimental protocols, no statistically significant differences were observed at T0 or T20 m, and STT 1 values were statistically lower in the ACP + MET than the ACP protocol at the other data points. In the ACP + MET group, at T40 m, 100% of dogs showed STT 1 readings lower than 15 mm/min. This finding is clinically relevant as it can predispose dogs to corneal injuries. The major reduction in tear production due to the ACP + MET protocol proves the need for adequate corneal hydration, particularly to discourage its use in animals with altered tear production. The data obtained provide important information helping clinicians to better manage the drug’s effects on tear production.